A collaborative clinical placement model for physiotherapy students results in equivalent (or greater) direct patient care activity than that delivered by physiotherapists alone: an observational study. (2nd January 2023) - Stoikov, Susan; Gooding, Mark; Shardlow, Kassie; Maxwell, Lyndal; Butler, Jane; Kuys, Suzanne
ABSTRACT: Background: The demand for physiotherapy clinical placements is rising which requires innovative approaches and an understanding of clinical placement models. Objective: To determine physiotherapy student contribution to direct patient care activity during a collaborative clinical placement model. Secondary aims determined the impact of clinical area and clinical educator to student (CE:student) ratio and if a group of students could reach equivalent direct patient care activity of a junior or senior physiotherapist. Method: Physiotherapy student, and junior and senior physiotherapist occasions of service (OOS) were collected from five Queensland Public Health Sector hospital information management systems from four physiotherapy clinical areas (i.e. cardiorespiratory, musculoskeletal, neurorehabilitation, and orthopedics). Number of days of clinical activity was recorded to provide average OOS/day. Results: Across a 5-week clinical placement a group of physiotherapy students in a collaborative clinical placement model provided on average 10.6 OOS/day (95%CI 10.1–11.2). In three (75%) clinical areas, a group of students participating in higher CE:student ratios produced more OOS/day. Clinical area and CE:student ratio predicted 39% of the variance in student average OOS/day. On average a group of students reached the equivalent direct patient care activity of a junior and senior physiotherapist by week two of a 5-week clinical placement. Conclusion: Physiotherapy students in a collaborative clinical placement model met or exceeded the direct patient care activity of a physiotherapist, irrespective of clinical area and CE:student ratio.